Influence of molecular flexibility on DNA radiosensitivity: a simulation study - Viduna, D; Hinsen, K; Kneller, G (Physical review. E, Statistical physics, plasmas, fluids, and related interdisciplinary topics, 2000)
Radiation damage in DNA is caused mainly by hydroxyl radicals which are generated by ionizing radiation in water and removing hydrogen atoms from the DNA chain. This damage affects certain nucleotide sequences more than others due to differences in the local structure of the DNA chains. This sequence dependence has been analyzed experimentally and calculated theoretically for a rigid DNA model. In this paper we take into account the flexibility of the DNA chain and show how it modifies the strand breakage probabilities. We use a simple harmonic model for DNA flexibility which permits the study of a long (68 base pair) fragment with modest computational effort. The essential influence of flexibility is an increased breakage probability towards the ends of the fragment, which can also be identified in the experimental data.
Keywords: Computer Simulation; konformace nukleové kyseliny; pravděpodobnost; DNA Damage; DNA; Hydrogen; poškození DNA; vodík; tolerance záření; Pliability; Probability; Radiation Tolerance; Nucleic Acid Conformation; počítačová simulace; ohebnost (fyzika)